2021
DOI: 10.1186/s12960-021-00584-1
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and depression among psychiatry residents during COVID-19 pandemic

Abstract: Very few studies have been concerned with assessing the prevalence of burnout and depressive symptoms, especially during an infectious outbreak on non-frontline health care workers, such as a psychiatrist. In such instances, the role of psychiatrists and other mental health providers as a source of psychological support to the public and frontline workers is indispensable and valuable. This study aims to assess the prevalence of burnout and depressive symptoms, and their correlation, during the COVID-19 pandem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 32 publications
2
44
0
8
Order By: Relevance
“…Several studies have found that some sociodemographic factors (such as age, gender, children, marital status, job contract, contact with the customer, seniority, level of education, and sick leaves in the last year) constituted significant predictors for burnout in healthcare and non-healthcare workers during the pandemic [18,[33][34][35]. Thus, we expect that our sample of Spanish commerce workers exhibit similar burnout levels to their foreign peers.…”
Section: Hypothesis 3 (H3mentioning
confidence: 87%
See 1 more Smart Citation
“…Several studies have found that some sociodemographic factors (such as age, gender, children, marital status, job contract, contact with the customer, seniority, level of education, and sick leaves in the last year) constituted significant predictors for burnout in healthcare and non-healthcare workers during the pandemic [18,[33][34][35]. Thus, we expect that our sample of Spanish commerce workers exhibit similar burnout levels to their foreign peers.…”
Section: Hypothesis 3 (H3mentioning
confidence: 87%
“…In that case, we also obtained significant results for all variables considered, except for education, in line with the findings of previous studies. Women presented higher levels of burnout than men [30], married participants exhibited lower levels of burnout than single or divorced participants, younger and less experienced employees displayed higher levels of burnout than older employees [16,35], having children represented a protective factor against burnout [34], and finally, having taken a sick leave was related to higher burnout levels [38,39]. The conclusion that we can obtain from our study regarding the influence of sociodemographic variables on burnout is that even with significant differences between the groups, these types of variables are not capable of predicting, in an acceptable way, burnout that a worker can experience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stress during a pandemic, associated with a change in life in almost every aspect, fear of illness, death and other psychosocial factors [7,49,165], can activate the stress axis [46], affect the severity of inflammation in the brain and, consequently, its structural and functional changes [55,65,71,218]. Research confirms that females, the healthcare professionals, elderly individuals, children, college students and psychiatric patients are in the group at increased risk of developing depressive disorders during the COVID-19 pandemic [151,[219][220][221][222][223].…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados resaltan la imperiosa necesidad de atender al PS que ha sufrido de COVID-19 ya que su salud física y mental pueden estar deterioradas lo que puede implicar un riesgo para la seguridad de los pacientes (Halla et al, 2016) ya que pueden cometer errores en su labor, debido a afecciones cognitivas, emocionales y fisiológicas (Macaya & Aranda, 2020). Y verse mermado su bienestar en general, debido a que, a mayor presencia de burnout, menores niveles de bienestar psicológico (Amutio et al, 2008) y mayor riesgo de sufrir depresión (Alkhamees et al, (2021).…”
Section: Discussionunclassified
“…Se menciona que tanto la depresión como el burnout pueden manifestarse a través de fatiga, irritabilidad y una reducción en las funciones cognitivas, lo que puede crear un ambiente de trabajo bajo presión, con menor calidad en el cuidado de los pacientes, lo que puede colocar al PS en un riesgo mayor de cometer errores. Alkhamees et al (2021) en su estudio realizado en Arabia Saudita con PS en pandemia de COVID-19, encontraron que aquellos que sufren de burnout tienen 8.88 más probabilidad de presentar síntomas de depresión. Se menciona que los factores que contribuyen a presentar mayores niveles de burnout se encuentra el ser soltero o divorciado, ser residente de los primeros dos años en la especialidad médica y el haber recibido ayuda en salud mental en los últimos dos años.…”
Section: Burnout En Psunclassified